The design and fabrication of two portal vein flow phantoms by different methods. Issue 2 (16th January 2014) - Yunker, Bryan E.; Dodd, Gerald D.; Chen, S. James; Chang, Samuel; Lanning, Craig J.; Scherzinger, Ann L.; Shandas, Robin; Feng, Yusheng; Hunter, Kendall S.
Abstract : Purpose: : This study outlines the design and fabrication techniques for two portal vein flow phantoms. Methods: : A materials study was performed as a precursor to this phantom fabrication effort and the desired material properties are restated for continuity. A three‐dimensional portal vein pattern was created from the Visual Human database. The portal vein pattern was used to fabricate two flow phantoms by different methods with identical interior surface geometry using computer aided design software tools and rapid prototyping techniques. One portal flow phantom was fabricated within a solid block of clear silicone for use on a table with Ultrasound or within medical imaging systems such as MRI, CT, PET, or SPECT. The other portal flow phantom was fabricated as a thin walled tubular latex structure for use in water tanks with Ultrasound imaging. Both phantoms were evaluated for usability and durability. Results: : Both phantoms were fabricated successfully and passed durability criteria for flow testing in the next project phase. Conclusions: : The fabrication methods and materials employed for the study yielded durable portal vein phantoms.